Harassment in the Purview of Social Media: A Cross-Sectional Analysis of Youth in District Dir Lower - Shah, Nasar; Zada, Hammad; Bibi, Asma (Pakistan Languages and Humanities Review, 2022)
The current study was carried out solely to investigate the part social media plays in encouraging youth harassment, which then contributes to deviation from the established social norms. A sample size of 354 respondents was chosen at random to collect primary data for that using a structured questionnaire technique. The primary data was also put into SPSS for additional descriptive and inferential statistical analysis. Based on the study’s findings, it was determined that girls in the study area were more likely than men to engage in online harassment and that excessive use of social media among young people can also contribute to physical and verbal abuse. Peer groups also encouraged teens to ignore wrongdoing while failing to properly socialize them at home and in school. With the aforementioned results in mind, the government should immediately implement these policies to resolve the study’s premises in order to engage the next generation in more constructive discussion about sustainable development. Parents should also pay attention to their children’s development in terms of proper check-and-balance practices on a weekly basis, along with proper socialization, to help them subdue harassment, a tumbling factor in today’s society, according to some recommendations made in light of the current study.